Corona blue among us: associations between risk perception, visits to urban spaces, and mental health in Seoul, Korea and Shanghai, China - Hyungchul Chung; Jaekyung Lee; Seul Lee; Jiwon Lee; Tae-Hyoung Tommy Gim; Yunmi Park (Journal of Asian Architecture and Building Engineering)
The so-called “Corona Blue” decline in mental health after the COVID-19 outbreak. This study examines how COVID-19 risk perception affects mental health via urban space usage in Seoul, Korea, and Shanghai, China. It uniquely explores direct PR-MH and OS-MH effects, along with indirect effects mediated by pandemic-driven changes in urban space utilization. Results reveal that visits to urban destinations and open spaces mediate the relationship between perceived risk and MH, with differing significance levels between the two cities. In Seoul, disruptions in daily life negatively affected mental health through decreased interactions with urban destinations and outdoor spaces, with a statistically significant impact on stress through urban destinations. This suggests that maintaining access to and engagement with these spaces is crucial for mental health during crises. Conversely, Shanghai showed indirect effects predominantly through perceptions of safety, which significantly influenced anxiety levels through urban destinations, but did not manifest similarly through interactions with outdoor spaces. Caution in interpretation is necessary for better generation, but the outcomes of this study underscore the importance of considering cultural, historical, and political contexts in understanding the varying impacts of future pandemic policies on mental health.